Iterative Object Localization Algorithm Using Visual Images with a Reference Coordinate. (4th September 2008) - Park, Kyoung-Su; Lee, Jinseok; Stanaćević, Milutin; Hong, Sangjin; Cho, We-Duke
Abstract : We present a simplified algorithm for localizing an object using multiple visual images that are obtained from widely used digital imaging devices. We use a parallel projection model which supports both zooming and panning of the imaging devices. Our proposed algorithm is based on a virtual viewable plane for creating a relationship between an object position and a reference coordinate. The reference point is obtained from a rough estimate which may be obtained from the preestimation process. The algorithm minimizes localization error through the iterative process with relatively low-computational complexity. In addition, nonlinearity distortion of the digital image devices is compensated during the iterative process. Finally, the performances of several scenarios are evaluated and analyzed in both indoor and outdoor environments.